Demographic Change in Asia : The Impacton Optimal National Saving, Investment, and the Current Account - McDonald, Ian (IMF Working Papers; Working Paper, 2000)
This paper calculates the levels of optimal national saving, investment, and the current account balance for five Asian economies-Hong Kong SAR, Japan, Singapore, Malaysia, and the Philippines-for the period 1997-2050 using a simulation approach. These calculations show the sensitivity of results to changing demographic structures on employment participation, labor productivity; and consumption demands. In particular, the simulations reveal that variations in prospective demographic change across economies cause considerable variations in the patterns of optimal national saving rates.